Review on per- and polyfluoroalkyl substances exposure, thyroid function, and mechanisms of action in mothers and infants - Lemin GONG; Zhongwu LU; Yuhan ZHOU (环境与职业医学)
Due to the outstanding hydrophobic and oleophobic properties, per- and polyfluoroalkyl substances (PFAS) are widely used in daily life and frequently detected in the environment. PFAS can enter the human body through water, food, and air exposure and accumulate in the human body. Epidemiological and toxicological evidence suggest that PFAS have endocrine-disrupting properties and may cause thyroid dysfunction by altering the hormonal homeostasis of the thyroid. This in turn affects the body's normal physiological functions, such as the physical growth and neurodevelopment in infants. Pregnancy and early life are special physiological stages, and the special dietary and lifestyle habits of this period make mothers and infants more likely to be exposed to PFAS and more susceptible to PFAS. Therefore, the exposure levels of PFAS and their effects on the thyroid function of mothers and infants were summarized in this review. Possible mechanisms of action by which PFAS may affect thyroid function were also summarized, aiming to provide a theoretical basis for the development of environmental standards and safety limits for PFAS.